Booster vaccines dose reduced mortality in hospitalized COVID-19 patients requiring oxygen supplementation: Evidence from the Beijing Omicron outbreak - Xinrui Wang; Yi Zhang; Chong Huang; Hui Yang; Chunguo Jiang; Xiaojia Yu; Rui Zhao; Jun Hong; Yi Zhang; Yushu Wang; Rui Zhao; Zhuoling An; et al. (Taylor & Francis Group, 2024)
To assess the impact of vaccines on clinical outcomes among hospitalized COVID-19-infected patients requiring oxygen supplementation during the Beijing Omicron outbreak. We conducted a retrospective cohort study at Beijing Chaoyang Hospital, Capital Medical University, from November 15, 2022, to March 31, 2023. Vaccination statuses were categorized into 3 doses, 2 doses, and unvaccinated (0 dose). The primary outcome was 28-day all-cause mortality. Secondary outcomes included poor outcomes, intensive care unit admission, cardiovascular thromboembolism events, and hospital readmission. Among the included patients, 117 were 2 doses, 285 received booster doses, and 503 were unvaccinated. After propensity score inverse probability weighting, the 3 doses group showed a significantly lower 28-day all-cause mortality compared to the unvaccinated group (inverse probability of treatment weighting-adjusted HR: 0.64, 95% CI: 0.50-0.81). No significant difference was observed in all-cause mortality between the 2 doses and unvaccinated groups. No significant differences were observed in secondary outcome analyses when comparing the 3 doses or 2 doses group to the unvaccinated group. Subgroup analysis revealed significant benefits of booster vaccination in patients with shorter symptom duration, lower Charlson Comorbidity Index, and without immunosuppression status. Our study highlights the significant reduction in all-cause mortality among hospitalized Omicron-infected patients who received a third dose vaccine. These findings underscore the importance of prioritizing booster vaccinations, especially among the elderly. Further research is warranted to confirm and extend these observations.